The Effect Of Good Corporate Governance on Financial Performance in PT X - Nuryadi Nuryadi; Lis Setyowati; Syamsul Arifin; Siswohadi Siswohadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This paper aims to The Effect Of Good Corporate Governance On Financial Performance In PT X. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 2 hypotheses are while the other is accepted. Research limitations/implications: Variables considered in this transparency of financial statements, management of alms funds and social funds, the reputation of the foundation, trust. The scope of analysis techniques used are multiple linear regression, F significance test, t significance test, multiple correlation coefficient (R), and multiple determination coefficient (R2). Practical implications: Results show that from the 2 hypotheses proposed. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study.